Metode Penafsiran al-Qur'an: Kajian kritis terhadap ayat-ayat yang beredaksi mirip - BAIDAN, Nashruddin (Pustaka Pelajar, 2002)
Metode Penafsiran al-Qur'an: Kajian kritis terhadap ayat-ayat yang beredaksi mirip